Anemia in young pregnant women: A cross-sectional study in Indonesia - Kuntari, Titik; Supadmi, Sri (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Background: The prevalence of anemia among pregnant women in Indonesian remains high at 48.9%, with the highest rates observed among young mothers aged 15-24 years. Anemia is associated with adverse outcomes for both mothers and their children. Understanding the determinants of anemia in young mothers is crucial for taking preventive measures. However, there are currently no national studies in Indonesia on the prevalence and risk factors of anemia in pregnant women aged 15 to 24 years. Objective: To measure the prevalence and factors associated with anemia in young pregnant women in Indonesia. Methods: This cross-sectional study utilized on secondary data from the 2018 Basic Health Research (Riset Kesehatan Dasar= Riskesdas). The subject of this research were pregnant women aged 15 to 24 years who participated in Riskesdas 2018 and had independent variables data including hemoglobin measurement data, age, education, residence, occupation, travel time to health facilities, age at first pregnancy, ownership of the maternal and child health (MCH) handbook, history of previous abortion, gestational age, number of iron supplement tablets, supplementary feeding, and chronic energy deficiency. Univariate analysis was conducted to analyse the subject characteristics and hemoglobin data, while chi-square and logistic regression were used to determine factors associated with anemia in young pregnant women Results: The study found that 36.2% of young pregnant women had anemia. The incidence of anemia was associated with gestational age but not with other factors. Pregnancy in the first trimester poses the highest risk compared to other trimesters (cOR=3.89; 95%CI:1.47-10.30; p=0.006), as confirmed by multivariate analysis (aOR=4.44; 95%CI: 1.41-13.95; p=0.01). Conclusion: Anemia affects 36.2% of pregnant women aged 15 to 24 years in Indonesia. The risk of anemia in young pregnant women is significantly associated with gestational age with the first trimester being the most critical period.